A study of ecological sanitation as an integrated urban water supply system: case study of sustainable strategy for Kuching City, Sarawak, Malaysia - Mah, Yau Seng; Frederik Josep, Putuhena; Puong, Ling Law; Salim, Said (ResearchGate, 2009)
A city consumes a large amount of water. Urban planning and development are becoming more compelling due to the fact of growing competition for water, which has lead to an increasing and conflicting demand. As such, investments in water supply, sanitation and water resources management is a strong potential for a solid return. A pilot project of greywater ecological treatment has been established in Kuching city since 2003. Such a treatment facility opens up an opportunity of wastewater reclamation for reuse as secondary sources of water for non-consumptive purposes. This paper aims to explore the potential of the intended purposes in the newly developed ecological treatment project. By utilizing the Wallingford Software model, InfoWorks WS (Water Supply) is employed to carry out a hydraulic modeling of a hypothetical greywater recycling system as an integrated part of the Kuching urban water supply, where the greywater is treated, recycled and reused in the domestic environment. The modeling efforts have shown water savings of about 40% from the investigated system reinstating that the system presents an alternative water source worth exploring in an urban environment.